A method and application of CO2 laser-induced synthesis of jujube-shaped heterostructure electrocatalyst
CoS/SnO2@C electrocatalyst with a jujube-like heterostructure was prepared by CO2 laser induction synthesis technology, which solved the problem of slow kinetics of oxygen reduction and oxygen evolution reactions in lithium oxygen batteries, and achieved efficient electrocatalytic performance and excellent Cyclic stability.
Patent Information
- Application Number
- CN202410438488.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-12
- Publication Date
- 2025-02-14
- Estimated Expiration
- 2044-04-12
AI Technical Summary
The kinetics of existing lithium oxygen batteries are slower in oxygen reduction and oxygen evolution reactions, resulting in high overpotential and poor electrocatalytic performance, limiting the practical application of lithium oxygen batteries.
The CoS/SnO2@C electrocatalyst with a jujube-like heterostructure was prepared by CO2 laser induced synthesis technology. The electrocatalyst was prepared by a two-step method of hydrothermal reaction and CO2 laser induction to form a carbon-based heterojunction supported by CoS and SnO2. The synergistic effect of interface charge distribution and active sites is optimized.
The efficient electrocatalytic performance of the cathode electrocatalyst of the lithium oxygen battery is achieved, which significantly improves the activity of oxygen reduction reaction and oxygen evolution reaction, and improves the specific capacity and cycle stability of the battery.
Smart Images

Figure CN118299575B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a method for synthesizing a jujube-shaped heterogeneous structure electrocatalyst by CO2 laser induction and application. Background Art
[0002] Against the backdrop of accelerating global energy consumption, electricity, as a sustainable and eco-friendly new energy source, is gradually gaining attention. Unlike traditional fossil energy, it does not produce large amounts of carbon dioxide and other harmful gases, and causes less pollution to the environment. At the same time, the renewability of electricity also makes it a reliable energy option. It can be generated through renewable energy sources such as solar energy and wind energy, thereby reducing dependence on limited resources. In addition, with the continuous advancement of technology, the storage and transmission efficiency of electricity is also constantly improving, making its application more extensive and convenient. Therefore, the research and development of energy storage equipment and technological innovation of electricity are imminent.
[0003] Lithium-oxygen batteries are expected to be a new trend in energy storage due to their low cost and green active cathode materials (O2). The electrochemical reaction mechanism of lithium-oxygen batteries includes two processes: the oxygen reduction reaction (ORR) to form Li2O2 during discharge and the decomposition of the discharge products into Li during charge. + However, the accumulation of insulating and insoluble discharge products (Li2O2) hinders the diffusion of oxygen and charge transfer on the cathode, resulting in high overpotential and especially slow kinetics of ORR and OER on the cathode, which will essentially limit the practical application of Li-O batteries.
[0004] Tin (Sn)-based electrocatalysts have superior interactions with oxygen intermediates, such as tin dioxide (SnO2), which can fine-tune the Sn site structure and change the oxygen reduction reaction and Li + The chemical environment of the active sites in the electrocatalyst for the oxygen evolution reaction with O2 promotes the activity and efficiency during the chemical reaction, which is of great significance to improving the efficiency of the electrocatalytic reaction. However, a single compound has defects such as poor conductivity, easy aggregation and difficult exposure of active sites, which leads to slow electron transfer and ion diffusion. Transition metal sulfides have attracted much attention in the field of energy storage due to their rich active centers, suitable electronic band structure, high specific capacity, excellent mechanical and thermal stability and good conductivity. Transition metal sulfides and SnO2 form heterojunctions with better interfacial charge distribution and synergistic effects between different active sites, which can promote reaction kinetics and thus improve the electrocatalytic activity of oxygen reaction. However, at present, transition metal sulfide and SnO2 composite catalytic materials are usually prepared by high-temperature pyrolysis, and the obtained materials often produce agglomeration, which is not conducive to the exposure of active sites and affects the electrocatalytic performance.
[0005] CO2 laser-induced synthesis technology is a cutting-edge material preparation technology. It cleverly uses CO2 lasers to accurately project laser energy to a specified position, providing powerful energy support for metal reduction. This technology not only has high reaction efficiency, but also precise position control, and does not require additional catalysts, effectively reducing production costs and reducing environmental pollution. At present, it has been widely used in the preparation of metal nanomaterials and oxides, showing great application potential in the fields of energy and environment.
[0006] Therefore, it is of great practical significance to develop a jujube-shaped heterojunction synthesized by CO2 laser as a bifunctional oxygen electrocatalyst for lithium-oxygen batteries. Summary of the invention
[0007] The technical problem to be solved by the present invention is to provide a method and application of CO2 laser-induced synthesis of jujube-shaped heterostructure electrocatalyst with simple synthesis, short time consumption, low energy consumption, good dispersibility, and excellent ORR and OER electrocatalytic performance. The electrocatalyst can be used to prepare lithium-oxygen battery cathode electrocatalyst.
[0008] The technical solution of the present invention is:
[0009] A method for synthesizing a jujube-shaped heterostructure electrocatalyst by CO2 laser induction comprises the following steps:
[0010] 1) After mixing a sulfur source and distilled water, a cobalt source, sodium citrate and a tin source are added and stirred evenly, wherein the sulfur source is L-cysteine, ammonium thiocyanate, thiourea or sulfur powder, the cobalt source is cobalt nitrate hexahydrate, cobalt chloride and cobalt acetylacetonate, and the tin source is stannous chloride, tin tetrachloride or stannous sulfate. A hydrothermal reaction is carried out at 150±10°C in a stainless steel autoclave for 6-8 h. After the reaction, the product is washed, centrifuged and vacuum dried overnight at room temperature to obtain an electrocatalyst precursor;
[0011] 2) The electrocatalyst precursor is ground into powder, evenly spread, and then induced by CO2 laser twice at a power of 4-8W in an air atmosphere; after the product is cooled to room temperature, the product is washed, then blow-dried and ground into powder to obtain a jujube-like heterostructure CoS / SnO2@C electrocatalyst.
[0012] Furthermore, the molar ratio of the sulfur source, the cobalt source, the tin source and the sodium citrate is 9:3:1:3.
[0013] Furthermore, the CO2 laser induced power is 8W.
[0014] Furthermore, the sulfur source is L-cysteine, the cobalt source is cobalt nitrate hexahydrate, and the tin source is stannous chloride; during the hydrothermal reaction, the molar volume ratio of the sulfur source to distilled water is 0.36 mol / L.
[0015] Furthermore, the hydrothermal reaction temperature was 150 °C and the reaction time was 6 h.
[0016] Furthermore, the CO2 laser induced scanning speed is 100-150 mms -1 .
[0017] Furthermore, in step 1), the washing is performed with distilled water for 2-3 times and then with ethanol for 2-3 times; in step 2), the washing is performed with distilled water for 2-3 times.
[0018] Furthermore, in step 2) drying, the drying temperature is 80±10°C and the drying time is 10-12 h.
[0019] The application of the jujube-like heterostructure electrocatalyst prepared by the method of CO2 laser-induced synthesis of jujube-like heterostructure electrocatalyst in the cathode electrocatalyst of lithium-oxygen batteries.
[0020] Furthermore, the catalyst is used as an oxygen reduction reaction electrocatalyst and / or an oxygen evolution reaction electrocatalyst.
[0021] The beneficial effects of the present invention are:
[0022] (1) The carbon-based CoS / SnO2@C electrocatalyst loaded with CoS and SnO2 of the present invention has a heterogeneous structure. There is an electronic interaction between CoS and SnO2 in the heterojunction region, which can obtain the best active site for the adsorption and activation of reactant molecules. The interface between CoS and SnO2 has a better interface charge distribution and a synergistic effect between different active sites, which can stimulate more electrons to participate in the oxygen reaction.
[0023] (2) The present invention utilizes CO2 laser induction, which is novel and has a simple preparation process. Compared with the slow and energy-consuming traditional high-temperature pyrolysis method, the reaction speed is fast, the energy consumption is low, and the carbon-based loaded CoS and SnO2 have good dispersion. By regulating the molar ratio of Co element and Sn element and the laser power, the synthesized CoS / SnO2@C electrocatalyst has a jujube-like heterostructure, which can further improve the electron transfer in the catalytic process and is beneficial to ion diffusion and catalytic reaction.
[0024] (3) The CoS / SnO2@C electrocatalyst of the present invention exhibits excellent electrocatalytic activity in both ORR and OER. The CoS / SnO2@C electrocatalyst is used as a cathode electrocatalyst for lithium-oxygen batteries, which exhibits high specific capacity and excellent cycle stability. The assembled lithium-oxygen battery has a high specific capacity and excellent cycle stability at 0.2 mA cm -2 At a current density of 0.1 mA cm, 223 stable cycles can be achieved. -2 At a current density of 3332 mAh g-1 The discharge specific capacity of this electrocatalyst is very good, and the electrocatalyst has very good application prospects as a cathode electrocatalyst in lithium-oxygen batteries. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 is a process flow chart of the present invention (corresponding to Example 3);
[0026] Figure 2 This is the SEM image of CoS / SnO2@C of the present invention (corresponding to Example 1);
[0027] Figure 3 The LSV curve of CoS / SnO2@C of the present invention (corresponding to Example 1); the electrolyte solution is: 0.1 mol L - 1 KOH; the scan rate of LSV test is: 5 mV s -1 ;
[0028] Figure 4 The LSV curve of CoS / SnO2@C of the present invention (corresponding to Example 1); the electrolyte solution is: 1 mol L - 1 KOH; the scan rate of LSV test is: 5 mV s -1 ;
[0029] Figure 5 This is the SEM image of CoS / SnO2@C of the present invention (corresponding to Example 2);
[0030] Figure 6 The LSV curve of CoS / SnO2@C of the present invention (corresponding to Example 2); the electrolyte solution is: 0.1 mol L - 1 KOH; the scan rate of LSV test is: 5 mV s -1 ;
[0031] Figure 7 The LSV curve of CoS / SnO2@C of the present invention (corresponding to Example 2); the electrolyte solution is: 1 mol L - 1 KOH; the scan rate of LSV test is: 5 mV s -1 ;
[0032] Figure 8 This is a SEM image of the jujube-shaped CoS / SnO2@C heterojunction electrocatalyst of the present invention (corresponding to Example 3);
[0033] Fig. 9 TEM image of the jujube-shaped CoS / SnO2@C heterojunction electrocatalyst of the present invention (corresponding to Example 3);
[0034] Fig.10 HRTEM image of the jujube-shaped CoS / SnO2@C heterojunction electrocatalyst of the present invention (corresponding to Example 3);
[0035] Fig.11 The LSV curve of the jujube-shaped CoS / SnO2@C of the present invention (corresponding to Example 3); the electrolyte solution is: 0.1 mol L -1 KOH; the scan rate of LSV test is: 5 mV s -1 ;
[0036] Fig.12 The LSV curve of the jujube-shaped CoS / SnO2@C of the present invention (corresponding to Example 3); the electrolyte solution is: 1 mol L -1 KOH; the scan rate of LSV test is: 5 mVs -1 ;
[0037] Fig.13 The cycle performance curve of the jujube-shaped CoS / SnO2@C as a cathode electrocatalyst for Li-O2 batteries according to the present invention (corresponding to Example 3); the current density is 0.2 mA cm -2 , limited to 500 mAh g -1 ;
[0038] Fig.14 The present invention (corresponding to Example 3) shows that the jujube-shaped CoS / SnO2@C is used as a cathode electrocatalyst for Li-O2 batteries at a current density of 0.1 mA cm -2 The first discharge curve diagram below;
[0039] Fig.15 This is the SEM image of CoS / SnO2@C of the present invention (corresponding to Example 4);
[0040] Fig.16 The LSV curve of CoS / SnO2@C of the present invention (corresponding to Example 4); the electrolyte solution is: 0.1 mol L -1 KOH; the scan rate of LSV test is: 5 mV s -1 ;
[0041] Fig.17 The LSV curve of CoS / SnO2@C of the present invention (corresponding to Example 4); the electrolyte solution is: 1 mol L - 1 KOH; the scan rate of LSV test is: 5 mV s -1 ;
[0042] Fig.18This is the SEM image of CoS / SnO2@CG of the present invention (corresponding to Example 1);
[0043] Fig.19 The LSV curve of CoS / SnO2@CG of the present invention (corresponding to Example 1); the electrolyte solution is: 0.1 molL -1 KOH; scan rate: 5 mV s -1 ;
[0044] Fig. 20 LSV curve of CoS / SnO2@CG of the present invention (corresponding to Example 1); the electrolyte solution is: 1 mol L -1 KOH; scan rate: 5 mV s -1 ;
[0045] Fig.21 This is the SEM image of CoS / SnO2@C of the present invention (corresponding to Example 2);
[0046] Fig. 22 This is the SEM image of CoS / SnO2@C of the present invention (corresponding to Example 3). DETAILED DESCRIPTION
[0047] Example 1
[0048] 1) First, 18 mmol L-cysteine (C3H7NO2S) was dissolved in 50 mL distilled water at room temperature. After dissolution, 6 mmol cobalt nitrate hexahydrate (Co(NO3)2·6H2O) and 6 mmol sodium citrate (C6H5Na3O7) were added, and finally 2 mmol stannous chloride (SnCl2) was added. After stirring for 30 min, the mixture was poured into a 100 mL stainless steel autoclave and hydrothermally reacted at 150°C for 6 h. After the reaction was completed, the product was cooled to room temperature, washed with distilled water for 3 times, then washed with ethanol for 3 times, centrifuged, and vacuum dried at room temperature 25°C for 12 h to obtain an electrocatalyst precursor.
[0049] 2) After the electrocatalyst precursor was ground into powder, it was evenly spread on a PI film with a thickness of 100 mm and marked with a CO2 laser with a laser power of 4 W and a scanning speed of 150 mm s. -1 Under the same conditions, CO2 laser induction was carried out twice in an air atmosphere. After the induction, the mixture was ground evenly, washed twice with distilled water, dried at 80 °C for 10 h, and ground into powder to obtain CoS / SnO2@C electrocatalyst.
[0050] The scanning electron microscope image of the CoS / SnO2@C electrocatalyst prepared in Example 1 of the present invention is as follows: Figure 2As shown, there is accumulation of spherical substances and the bionic red blood cell-like morphology is not obvious and aggregation occurs.
[0051] The ORR performance of CoS / SnO2@C electrocatalyst is shown in Figure 3 As shown, the initial potential value is 0.90 V and the half-wave potential value is 0.84 V. The limiting current density is 5.67 mA cm -2 .
[0052] The OER performance of CoS / SnO2@C electrocatalysts is shown in Figure 4 As shown in the figure, CoS / SnO2@C at a current density of 10 mA cm -1 The overpotential at is 335 mV.
[0053] Example 2
[0054] 1) First, 18 mmol L-cysteine (C3H7NO2S) was dissolved in 50 mL distilled water at room temperature. After dissolution, 6 mmol cobalt nitrate hexahydrate (Co(NO3)2·6H2O) and 6 mmol sodium citrate (C6H5Na3O7) were added, and finally 2 mmol stannous chloride (SnCl2) was added. After stirring for 30 min, the mixture was poured into a 100 mL stainless steel autoclave and hydrothermally reacted at 150°C for 6 h. After the reaction was completed, the product was cooled to room temperature, washed with distilled water for 3 times, then washed with ethanol for 3 times, centrifuged, and vacuum dried at room temperature 25°C for 12 h to obtain an electrocatalyst precursor.
[0055] 2) After the electrocatalyst precursor was ground into powder, it was evenly spread on a PI film with a thickness of 100 mm and marked with a CO2 laser with a laser power of 6 W and a scanning speed of 150 mm s. -1 Under the same conditions, CO2 laser induction was carried out twice in an air atmosphere. After the induction, the mixture was ground evenly, washed twice with distilled water, dried at 80 °C for 10 h, and ground into powder to obtain CoS / SnO2@C electrocatalyst.
[0056] The scanning electron microscope image of the CoS / SnO2@C electrocatalyst prepared in Example 2 of the present invention is as follows: Figure 5 As shown, it can be observed that the spherical shape and the bionic red blood cell shape gradually become obvious, and the catalyst aggregation weakens.
[0057] The ORR performance of CoS / SnO2@C electrocatalyst is shown in Figure 6 As shown, the initial potential value is 0.93 V and the half-wave potential value is 0.86 V. The limiting current density is 5.72 mA cm -2 .
[0058] The OER performance of CoS / SnO2@C electrocatalysts is shown in Figure 7 As shown in the figure, CoS / SnO2@C at a current density of 10 mA cm -1 The overpotential at is 309 mV.
[0059] Example 3
[0060] 1) First, 18 mmol L-cysteine (C3H7NO2S) was dissolved in 50 mL distilled water at room temperature, and then 6 mmol cobalt nitrate hexahydrate (Co(NO3)2·6H2O) and 6 mmol sodium citrate (C6H5Na3O7) were added after dissolution, and finally 2 mmol stannous chloride (SnCl2) was added. After stirring for 30 min, the mixture was poured into a 100 mL stainless steel autoclave and hydrothermally reacted at 150°C for 6 h. After the reaction was completed, the product was cooled to room temperature and washed with distilled water for 3 times, then washed with ethanol for 3 times, centrifuged, and vacuum dried at room temperature 25°C for 12 h to obtain an electrocatalyst precursor.
[0061] 2) After the electrocatalyst precursor was ground into powder, it was evenly spread on a PI film with a thickness of 100 mm and marked with a CO2 laser with a laser power of 8 W and a scanning speed of 150 mm s -1 Under the same conditions, CO2 laser induction was carried out twice in an air atmosphere, and then the mixture was evenly ground, washed twice with distilled water, dried at 80 °C for 10 h, and ground into powder to obtain a jujube-like CoS / SnO2@C heterostructure electrocatalyst.
[0062] The scanning electron microscope image of the jujube-shaped CoS / SnO2@C electrocatalyst prepared in Example 3 of the present invention is as follows: Figure 8 As shown, it can be clearly seen that the bionic red blood cell shape and the spherical shape are closely connected, presenting a unique jujube-like surface morphology.
[0063] The transmission electron microscopy image of the jujube-shaped CoS / SnO2@C electrocatalyst prepared in Example 3 of the present invention is as follows: Fig. 9 As shown,
[0064] It can be clearly seen that the two particles, one large and one small, are closely connected together, and it can be preliminarily determined that this electrocatalyst has a heterogeneous structure.
[0065] The high magnification transmission electron microscopy image of the jujube-shaped CoS / SnO2@C electrocatalyst prepared in Example 3 of the present invention is as follows: Fig.10 As shown, two clear and obvious lattice fringes can be seen, and the lattice spacings of 0.29 and 0.26 nm correspond to the (100) crystal plane of CoS and the (101) crystal plane of SnO2, respectively, which proves that the CoS / SnO2@C electrocatalyst is a heterogeneous structure.
[0066] The ORR performance of the jujube-shaped CoS / SnO2@C electrocatalyst prepared in Example 3 of the present invention is as follows: Fig.11 As shown in Figure 2, the initial potential value is 0.96 V, the half-wave potential value is 0.88 V, and the maximum limiting diffusion current density is 6.39 mAcm -2 . CoS / SnO2@C has excellent ORR activity.
[0067] The OER performance of the jujube-shaped CoS / SnO2@C electrocatalyst prepared in Example 3 of the present invention is as follows: Fig.12 As shown in the figure, CoS / SnO2@C at a current density of 10 mA cm -1 The overpotential at 270 mV showed excellent OER activity.
[0068] The cycle performance curve measured by assembling the battery according to Example 3 is as follows: Fig.13 As shown, at a current density of 0.2 mAcm -2 and a capacity limit of 500 mAh g -1 Under these circumstances, the jujube-shaped CoS / SnO2@C heterojunction electrocatalyst can achieve 223 stable cycles.
[0069] The first discharge curve measured by assembling the battery according to Example 3 is as follows: Fig.14 As shown, at 0.1 mA cm -2 At a current density of 2.5 Å, CoS / SnO2@C has a high capacity of 3332 mAh g -1 The discharge capacity.
[0070] Comparative Example 1
[0071] CoS / SnO2@CG electrocatalyst was synthesized by thermal decomposition at 800℃ in Ar atmosphere.
[0072] 1) First, 18 mmol L-cysteine (C3H7NO2S) was dissolved in 50 mL distilled water at room temperature. After dissolution, 6 mmol cobalt nitrate hexahydrate (Co(NO3)2·6H2O) and 6 mmol sodium citrate (C6H5Na3O7) were added, and finally 2 mmol stannous chloride (SnCl2) was added and stirred for 30 min. After stirring, the above solution was placed in a 100 mL stainless steel autoclave and hydrothermally reacted at 150°C for 6 h. After the reaction, the product was cooled to room temperature and washed with distilled water 3 times and then with ethanol 3 times. After washing, it was vacuum dried at room temperature for 12 h to obtain the precursor.
[0073] 2) After the precursor is ground into powder, it is placed in a porcelain boat and pyrolyzed at 800°C in an Ar atmosphere for 2 h. After the pyrolysis, the evenly ground product is washed twice with distilled water. The experimental product is dried at 80°C for 10 h and ground into powder to obtain the CoS / SnO2@CG electrocatalyst.
[0074] The scanning electron microscope image of the CoS / SnO2@CG electrocatalyst prepared in Comparative Example 1 of the present invention is as follows: Fig.18 As shown in the figure, it can be observed that the CoS / SnO2@CG obtained by high-temperature pyrolysis has an irregular morphology and serious agglomeration occurs. This is conducive to material transport and electrolyte penetration. This also confirms the advantages of laser synthesis.
[0075] The ORR performance of the CoS / SnO2@CG electrocatalyst prepared in Comparative Example 1 of the present invention is as follows: Fig.19 As shown in Figure 2, the initial potential value of CoS / SnO2@CG is 0.85 V, which is much lower than that of CoS / SnO2@C (0.96 V). The half-wave potential value of CoS / SnO2@CG is 0.75 V, while the half-wave potential value of CoS / SnO2@C is 0.88 V, which is better than CoS / SnO2@CG. The limiting current density value of CoS / SnO2@CG is 5.78 mA cm -2 , which is lower than 6.39 mA cm of CoS / SnO2@C. -2 According to the above electrochemical tests, CoS / SnO2@C has better ORR activity than CoS / SnO2@CG.
[0076] The OER performance of the CoS / SnO2@CG electrocatalyst prepared in Comparative Example 1 of the present invention is as follows: Fig. 20 As shown in Figure 2, it can be seen that CoS / SnO2@C has a high current density of 10 mA cm -1 The overpotential value at 270 mV is much better than that of CoS / SnO2@CG (353 mV). The above electrochemical tests show that the electrochemical performance of the electrocatalyst prepared by the traditional pyrolysis strategy is far inferior to that of the electrocatalyst prepared by laser, which reflects the advantages of laser synthesis.
[0077] Comparative Example 2
[0078] 1) First, 18 mmol L-cysteine (C3H7NO2S) was dissolved in 50 mL distilled water at room temperature, and then 4 mmol cobalt nitrate hexahydrate (Co(NO3)2·6H2O) and 6 mmol sodium citrate (C6H5Na3O7) were added after dissolution, and finally 2 mmol stannous chloride (SnCl2) was added. After stirring for 30 min, the mixture was poured into a 100 mL stainless steel autoclave and hydrothermally reacted at 150°C for 6 h. After the reaction was completed, the product was cooled to room temperature, washed with distilled water 3 times, then washed with ethanol 3 times, centrifuged, and vacuum dried at room temperature 25°C for 12 h to obtain an electrocatalyst precursor.
[0079] 2) After the electrocatalyst precursor was ground into powder, it was evenly spread on a PI film with a thickness of 100 mm and marked with a CO2 laser with a laser power of 8 W and a scanning speed of 150 mm s -1 Under the same conditions, CO2 laser induction was carried out twice in an air atmosphere. After the induction, the mixture was ground evenly, washed twice with distilled water, dried at 80 °C for 10 h, and ground into powder to obtain CoS / SnO2@C electrocatalyst.
[0080] The scanning electron microscope image of the CoS / SnO2@C electrocatalyst prepared in Comparative Example 2 of the present invention is as follows: Fig.21 As shown in the figure, it can be observed that the spherical substances are accumulated and the bionic red blood cell-like substances are seriously adhered.
[0081] ORR performance of CoS / SnO2@C electrocatalyst: initial potential value is 0.89 V, half-wave potential value is 0.78 V. Limiting current density is 5.61 mA cm -2 .
[0082] OER performance of CoS / SnO2@C electrocatalyst: CoS / SnO2@C at a current density of 10 mA cm -1 The overpotential at is 328 mV.
[0083] Comparative Example 3
[0084] 1) First, 18 mmol L-cysteine (C3H7NO2S) was dissolved in 50 mL distilled water at room temperature, and then 8 mmol cobalt nitrate hexahydrate (Co(NO3)2·6H2O) and 6 mmol sodium citrate (C6H5Na3O7) were added after dissolution, and finally 2 mmol stannous chloride (SnCl2) was added. After stirring for 30 min, the mixture was poured into a 100 mL stainless steel autoclave and hydrothermally reacted at 150°C for 6 h. After the reaction was completed, the product was cooled to room temperature and washed with distilled water for 3 times, then washed with ethanol for 3 times, centrifuged, and vacuum dried at room temperature 25°C for 12 h to obtain an electrocatalyst precursor.
[0085] 2) After the electrocatalyst precursor was ground into powder, it was evenly spread on a PI film with a thickness of 100 mm and marked with a CO2 laser with a laser power of 8 W and a scanning speed of 150 mm s -1 Under the same conditions, CO2 laser induction was carried out twice in an air atmosphere. After the induction, the mixture was ground evenly, washed twice with distilled water, dried at 80 °C for 10 h, and ground into powder to obtain CoS / SnO2@C electrocatalyst.
[0086] The scanning electron microscope image of the CoS / SnO2@C electrocatalyst prepared in Comparative Example 3 of the present invention is as follows: Fig. 22 As shown in the figure, it can be observed that the spherical material accumulates and the morphology of the bionic red blood cell-like material becomes obvious, and the adhesion phenomenon is weakened.
[0087] ORR performance of CoS / SnO2@C electrocatalyst: initial potential value is 0.94 V, half-wave potential value is 0.80 V. Limiting current density is 6.10 mA cm -2 .
[0088] OER performance of CoS / SnO2@C electrocatalyst: CoS / SnO2@C at a current density of 10 mA cm -1 The overpotential at is 303 mV.
[0089] Comparative Example 4
[0090] 1) First, 18 mmol L-cysteine (C3H7NO2S) was dissolved in 50 mL distilled water at room temperature, and then 6 mmol cobalt nitrate hexahydrate (Co(NO3)2·6H2O) and 6 mmol sodium citrate (C6H5Na3O7) were added after dissolution, and finally 2 mmol stannous chloride (SnCl2) was added. After stirring for 30 min, the mixture was poured into a 100 mL stainless steel autoclave and hydrothermally reacted at 150°C for 6 h. After the reaction was completed, the product was cooled to room temperature and washed with distilled water for 3 times, then washed with ethanol for 3 times, centrifuged, and vacuum dried at room temperature 25°C for 12 h to obtain an electrocatalyst precursor.
[0091] 2) After the electrocatalyst precursor was ground into powder, it was evenly spread on a PI film with a thickness of 100 mm and marked with a CO2 laser with a laser power of 10 W and a scanning speed of 150 mm s. -1 Under the same conditions, CO2 laser induction was carried out twice in an air atmosphere. After the induction, the mixture was ground evenly, washed twice with distilled water, dried at 80 °C for 10 h, and ground into powder to obtain CoS / SnO2@C electrocatalyst.
[0092] The scanning electron microscope image of the CoS / SnO2@C electrocatalyst prepared in Comparative Example 4 of the present invention is as follows: Fig.15 As shown, it can be observed that the catalyst is obviously accumulated, and the spherical shape and bionic red blood cell shape are not obvious.
[0093] The ORR performance of CoS / SnO2@C electrocatalyst is shown in Fig.16 As shown, the initial potential value is 0.95 V and the half-wave potential value is 0.87 V. The limiting current density is 5.05 mA cm -2 .
[0094] The OER performance of CoS / SnO2@C electrocatalysts is shown in Fig.17 As shown in the figure, CoS / SnO2@C at a current density of 10 mA cm -1 The overpotential at is 290 mV.
[0095] 1. The instruments used in the above embodiments and comparative examples are as follows
[0096] The electrocatalyst morphology was characterized using a scanning electron microscope (SEM, Hitachi S-4800). Transmission electron microscopy (TEM) was performed at 220 kV using a Talos F200S G2. A CO2 laser cutting system (SC-CO2-B30, total power of 30 W, laser wavelength of 10.6 µm) was purchased from Shanghai Suochang Optoelectronic Equipment Co., Ltd. The electrochemical test was performed using a Shanghai Chenhua CHI 660E device.
[0097] 2. Electrode Preparation and Modification
[0098] For ORR and OER, all electrochemical tests were performed using a conventional three-electrode system, including a working electrode, a reference electrode (Hg / HgO electrode), and a counter electrode (carbon rod). Before the electrochemical test, the bare working electrode was polished with alumina powders of different particle sizes (1.0, 0.3, and 0.05 μm, respectively) on a polishing cloth. It was then ultrasonically cleaned with dilute HNO3, ethanol, and distilled water (1 min each). In order to prepare the working electrode for ORR and OER performance tests, 5 mg of the jujube-like CoS / SnO2@C heterostructure electrocatalyst prepared in Example 3 was dispersed in distilled water and isopropanol, and then Nafion solution was added and ultrasonically treated for 3 h (500 μL distilled water / 500 μL isopropanol / 20 μL Nafion; electrocatalyst preparation concentration 5 mgmL -1 ) to obtain a uniform suspension. This suspension was drop-coated onto the working electrode and then dried at room temperature. For the ORR working electrode, a modified rotating disk electrode (RDE, d = 5.0 mm, A = 0.19625 cm 2), using 0.1 molL -1 KOH solution was used as the electrolyte. For comparison, commercial 20 wt% Pt / C was used as the electrocatalyst by the same method. For OER, the working electrode was a glassy carbon electrode using 1 molL -1 KOH solution was used as the electrolyte. For comparison, commercial RuO2 was used as the electrocatalyst by the same method.
[0099] All electrochemical tests were performed on a CHI660E electrochemical workstation (Shanghai Chenhua). According to the Nernst equation (E(V vs. RHE) = E(V vs. Hg / HgO) + 0.098 V + 0.059 × pH), all potentials in this paper were calibrated to the reversible hydrogen electrode (RHE).
[0100] In summary, this paper develops a bifunctional oxygen electrocatalyst with a jujube-like heterostructure synthesized by CO2 laser and uses it as a high-performance Li-O2 battery cathode catalyst to achieve efficient electrocatalytic activity. The CoS / SnO2@C electrocatalyst has higher ORR / OER catalytic efficiency than commercial Pt / C / RuO2. At the same time, CoS / SnO2@C as a Li-O2 battery cathode electrocatalyst has a higher current density of 0.2 mA cm -2 223 stable cycles can be achieved at 0.1 mA cm -2 At a current density of 2.5 Å, CoS / SnO2@C has a high capacity of 3332 mAh g -1 The discharge capacity of Li-O2 batteries with excellent discharge capacity and cycle stability require stable and efficient ORR and OER bifunctional electrocatalysts for practical applications. Therefore, the novel synthesis method proposed in the present invention, that is, the method of synthesizing electrocatalysts by CO2 laser technology, has the advantages of being fast and simple. The synthesized CoS / SnO2@C bifunctional oxygen electrocatalyst provides ideas for the design and preparation of high-performance Li-O2 batteries. In addition, the method is simple to synthesize and preliminary results show that the prepared electrocatalyst is a promising ORR and OER bifunctional electrocatalyst, which can be used in metal-air batteries, fuel cells and electrocatalysis.
[0101] The above are only specific embodiments of the present invention and are not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for synthesizing a jujube-shaped heterostructure electrocatalyst by CO2 laser induction, characterized in that: The steps include: 1) After mixing a sulfur source and distilled water, a cobalt source, sodium citrate and a tin source are added and stirred evenly, wherein the sulfur source is L-cysteine, ammonium thiocyanate, thiourea or sulfur powder, the cobalt source is cobalt nitrate hexahydrate, cobalt chloride or cobalt acetylacetonate, and the tin source is stannous chloride, tin tetrachloride or stannous sulfate. A hydrothermal reaction is carried out at 150±10°C in a stainless steel autoclave for 6-8 h. After the reaction, the product is washed, centrifuged and vacuum dried overnight at room temperature to obtain an electrocatalyst precursor; The molar ratio of the sulfur source, the cobalt source, the tin source and the sodium citrate is 9:3:1:3; 2) The electrocatalyst precursor is ground into powder, evenly spread, and then induced by CO2 laser twice at a power of 8 W in an air atmosphere; after the product is cooled to room temperature, the product is washed, then blow-dried and ground into powder to obtain a jujube-like heterostructure CoS / SnO2@C electrocatalyst.
2. The method for CO2 laser-induced synthesis of jujube-shaped heterostructure electrocatalyst according to claim 1, characterized in that: The sulfur source is L-cysteine, the cobalt source is cobalt nitrate hexahydrate, and the tin source is stannous chloride; during the hydrothermal reaction, the molar volume ratio of the sulfur source to distilled water is 0.36 mol / L.
3. The method for CO2 laser-induced synthesis of jujube-shaped heterostructure electrocatalyst according to claim 1, characterized in that: The hydrothermal reaction temperature was 150 °C and the reaction time was 6 h.
4. The method for CO2 laser-induced synthesis of jujube-shaped heterostructure electrocatalyst according to claim 1, characterized in that: CO2 laser induced scanning speed is 100-150 mms -1 .
5. The method for CO2 laser-induced synthesis of jujube-shaped heterostructure electrocatalyst according to claim 1, characterized in that: In step 1), the washing is performed 2-3 times with distilled water and then 2-3 times with ethanol; in step 2), the washing is performed 2-3 times with distilled water.
6. The method for CO2 laser-induced synthesis of jujube-shaped heterostructure electrocatalyst according to claim 1, characterized in that: Step 2) During drying, the drying temperature is 80±10°C and the drying time is 10-12 h.
7. Use of a jujube-shaped heterostructure electrocatalyst prepared by the method for synthesizing a jujube-shaped heterostructure electrocatalyst induced by CO2 laser as claimed in claim 1 in a cathode electrocatalyst for a lithium-oxygen battery.
8. Use of the jujube-shaped heterostructure electrocatalyst prepared by the method for synthesizing jujube-shaped heterostructure electrocatalyst induced by CO2 laser according to claim 7 in a cathode electrocatalyst of a lithium oxygen battery, characterized in that: The catalyst is used as an oxygen reduction reaction electrocatalyst and / or an oxygen evolution reaction electrocatalyst.
Citation Information
Patent Citations
Preparation method of 3D porous cobalt-tin-molybdenum three-metal catalyst
CN110560094A
Preparation method and application of cobalt sulfide / tin dioxide composite film and dye-sensitized solar cell thereof
CN115831616A